Physical conditions of the ‘light’ core formation and thermonuclear heat source deep inside the Earth - Sobolev, V. V.; Bilan, N. V. (Naukovyi Visnyk NHU, 2018)
Purpose. Experimental research into the physical model of the Earth’s core formation in the center of gas‑dust spiral vortex and numerical assessment of the physical conditions associated with the development of thermonuclear reactions in the Earth’s core. Methodology. Analysis of the main points of conventional conceptions, their principal merits and drawbacks which delineate their potential possibilities. Experimental studies implementing shock‑wave treatment of porous materials in cylindrical containers. Numerical assessment of the physical conditions that initiate thermonuclear reactions in the Earth’s core. Findings. It is extremely important to choose the model of the Earth formation with originally “light” core for several reasons. First, it provides a physically grounded mechanism of the thermonuclear heat source formation;second, the process of the Earth transition to equilibrium state inevitably creates conditions for mechanical, physical and chemical activity of elements in geospheres. Numerical assessment was performed to estimate the main conditions which are necessary for thermonuclear heating of the Earth’s central bulk – to determine the deuterium nuclei concentration and the respective temperatures. Originality. The authors suggested a model describing formation of the initially “light” core of the Earth. Experiments allowed studying some physical peculiarities of spiral vortices initiation and development. Regularities of change in plasma parameters, core temperature and thermonuclear energy release have been established in reference to the Earth’s age. Practical value. The obtained results will be useful for studying such important planetary geological phenomena as matter differentiation and formation of spheres inside the planet, as well as heat flow distribution in its bulk.
Keywords: gas and dust matter, spiral vortex, the Earth’s core, thermonuclear reactions, the Earth’s age